Investigating the role of teaching pronunciation to learners of english as a second language - Alves, Lyvya Pereira de Azevedo (2022)
Pronunciation is one of the features involved in the process of learning a language. Literature review has suggested that learning pronunciation is crucial for oral communication in a language, as people can only be understood if they are intelligible. In order to improve understanding of the role of pronunciation, the present paper aimed at reviewing relevant studies that examined how second language teachers perceive pronunciation in the context of language learning. Analysis of these studies reveals that although the area of pronunciation has been neglected over the years, especially when compared to other language features such as vocabulary and grammar, its value is undeniable. In order to understand teachers’ beliefs on pronunciation teaching and its implications for second language learning, a qualitative study was carried out and the main results showed that language teachers believe in the importance of teaching pronunciation to their students, mainly because it directly affects their communication skills; however, they do not consider pronunciation as important as grammar and vocabulary teaching. Furthermore, the present study aims to explore the reasons for the insecurities teachers may feel when teaching pronunciation, and how schools could support these teachers to achieve better performance in their classes.